Environmental Reclamation And Monitoring Of The Abandoned Belle Eldridge Mine Near Deadwood, SD - A. Davis; C. Webb; J. Sorensen (Society for Mining, Metallurgy & Exploration, 2007)
The abandoned Belle Eldridge Mine near Deadwood, South Dakota, is on land controlled by the U.S. Bureau of Land Management (BLM). The mine produced lead and zinc during the first half of the 1900s. Because of acidic drainage and elevated levels of metals in tailings and waste rock, the site was evaluated in 1998 and 1999. After evaluation, the mine was remediated during 1999-2001 by the BLM. Since remediation, values of pH in water samples have been nearly neutral and specific conductance values have been much lower than before remediation. The Grizzly Gulch forest fire of July, 2002, consumed much of the Belle Eldridge site and resulted in greater than normal erosion and sediment flushing during the months following the wildfire. Had the site not been remediated and the tailings emplaced within a capped repository, generation of acidity and off-site migration of heavy metals within sediments could have been severe at downstream locations.